p16 mutation spectrum in the premalignant condition Barrett's esophagus. - Thomas G Paulson; Patricia C Galipeau; Lianjun Xu; Heather D Kissel; Xiaohong Li; Patricia L Blount; Carissa A Sanchez; Robert D Odze; Brian J Reid (PLoS ONE, 2008)
Mutation, promoter hypermethylation and loss of heterozygosity involving the tumor suppressor gene p16 (CDKN2a/INK4a) have been detected in a wide variety of human cancers, but much less is known concerning the frequency and spectrum of p16 mutations in premalignant conditions.We have determined the p16 mutation spectrum for a cohort of 304 patients with Barrett's esophagus, a premalignant condition that predisposes to the development of esophageal adenocarcinoma. Forty seven mutations were detected by sequencing of p16 exon 2 in 44 BE patients (14.5%) with a mutation spectrum consistent with that caused by oxidative damage and chronic inflammation. The percentage of patients with p16 mutations increased with increasing histologic grade. In addition, samples from 3 out of 19 patients (15.8%) who underwent esophagectomy were found to have mutations.The results of this study suggest the environment of the esophagus in BE patients can both generate and select for clones with p16 mutations.